FINANCIAL RESULTS IN THE ACCOUNTING SYSTEM OF AGRIBUSINESS ENTERPRISES - GUTSALENKO, Liubov; MOLDOVAN, Myroslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the economic essence of the concept of "financial results". The current regulatory and legal framework was analyzed and it was noted that there is no interpretation of financial results in regulatory and legal documents. The scientific literature was studied and various approaches to revealing the content of the studied category were clarified. The opinion is supported that when defining the concept of "financial results" it is necessary to connect three aspects - essence, content and form of manifestation. A refined definition of the content of the researched category is proposed: financial results are an indicator of the performance of a business entity, which is defined as the difference between income and expenses for a certain reporting period and for certain types of economic activity, and after deduction of taxes is disclosed in the form of profit or loss. Internal and external factors influencing the formation of financial results of agricultural enterprises are determined. The composition of the financial results of agricultural enterprises, which are related to the implementation of agricultural activities, which involves the process of managing biological transformations in order to obtain agricultural products or additional biological assets, is noted. The influence of the evaluation of agricultural products and biological assets at fair value on the financial result was noted.  The characteristics of accounting accounts of financial results are revealed. It is conditioned on the objectivity of the return in the system of financial reporting indicators of information about extraordinary expenses and incomes related to compensation for losses from extraordinary events. It was noted that all information about the financial results of the agricultural enterprise should be useful for the needs of different groups of users. It is proposed to detail the financial results according to the types of activities of agricultural enterprises by entering the relevant analytical accounts on the sub-accounts of account 79 "Financial results".
Keywords: financial results; income; expenses; accounting; agricultural activity